2019
DOI: 10.1093/jee/toz152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex and Air Temperature on the Flight Capacity of Bradysia odoriphaga (Diptera: Sciaridae)

Abstract: Bradysia odoriphaga Yang & Zhang (Diptera: Sciaridae) is an important pest of Chinese chives. Information on the effects of biotic and abiotic factors on the flight performance of B. odoriphaga is crucial for understanding the pest’s ability to disperse and migrate. In this study, the effects of sex and air temperature on the flight performance of B. odoriphaga imagoes were assessed by tethering individual imagoes to computerized flight mills for a 10-h experiment. The results showed that the percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This study found that the lifespan of unmated female adults was significantly longer than that of unmated male adults ( Figure 4E). This may relate to the poor flight ability of females [39], which requires passive acceptance of flying males for mating. Therefore, the extended lifetime of females allows males more opportunities to find them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the lifespan of unmated female adults was significantly longer than that of unmated male adults ( Figure 4E). This may relate to the poor flight ability of females [39], which requires passive acceptance of flying males for mating. Therefore, the extended lifetime of females allows males more opportunities to find them.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the extended lifetime of females allows males more opportunities to find them. In addition, the females have a larger body and store much more energy than males [39]-another reason females can live longer than males. Females die soon after they mate and oviposit successfully, as the lifespan of mated females is significantly shorter than that of unmated females.…”
Section: Discussionmentioning
confidence: 99%